Computational Ship Design - Roh, Myung-Il.; Lee, Kyu-Yeul.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book offers an introduction to the fundamental principles and systematic methodologies employed in computational approaches to ship design. It takes a detailed approach to the description of the problem definition, related theories, mathematical formulation, algorithm selection, and other core design information. Over eight chapters and appendices the book covers the complete process of ship design, from a detailed description of design theories through to cutting-edge applications. Following an introduction to relevant terminology, the first chapters consider ship design equations and models, freeboard calculations, resistance prediction and power estimation. Subsequent chapters cover topics including propeller deign, engine selection, hull form design, structural design and outfitting. The book concludes with two chapters considering operating design and economic factors including construction costs and fuel consumption. The book reflects first-hand experiences in ship design and R&D activities, and incorporates improvements based on feedback received from many industry experts. Examples provided are based on genuine case studies in the field. The comprehensive description of each design stage presented in this book offers guidelines for academics, researchers, students, and industrial manufactures from diverse fields, including ocean engineering and mechanical engineering. From a commercial point of view the book will be of great value to those involved in designing a new vessel or improving an existing ship. .
Preface -- 1 Introduction -- 2 Analysis of Ship Owner's Requirements -- 3 Design Constraints -- 4 Estimation of Lightweight -- 5 Prediction of Resistance and Power -- 6 Selection of Main Engine -- 7 Determination of Principal Dimensions of Propeller -- 8 Estimation of Capacity of Cargo Hold -- 9 Calculation of Freeboard -- 10 Determination of Principal Dimensions -- 11 Hull Form Design -- 12 General Arrangement Design -- 13 Hull Structural Design -- 14 Outfitting Design -- 15 Economic Evaluation -- 16 Example of Determination of Principal Dimensions -- 17 Examples of Ship Design Model -- A.1. Introduction to optimum design -- A.2. Selective optimization methods -- A.3. Example of optimal dimension design -- A.4. Example of optimal arrangement design -- References -- Index. .
Keywords: Engineering design; Transportation engineering; Traffic engineering; Engineering mathematics; Engineering -- Data processing; Mathematics -- Data processing; Mathematical physics; Computer-aided engineering; Engineering Design; Transportation Technology and Traffic Engineering; Mathematical and Computational Engineering Applications; Computational Science and Engineering; Theoretical, Mathematical and Computational Physics; Computer-Aided Engineering (CAD, CAE) and Design